Database of Ichthyofauna in urban streams of Johor Bahru, Malaysia - Rei Itsukushima; Mohd Shalahuddin Adnan; Yuta Tomiyama; Yuichi Kano; Keigo Otsu; Muhamad Firdaus Zanorin (Biodiversity Data Journal)
Urbanisation leads to the degradation of ecosystems through various factors, such as the deterioration of water quality, changes in water and material cycles and the degradation of biological habitats. Amongst these, aquatic organisms are particularly affected by the loss of habitats due to river canalisation and the impacts of invasive species. It has been widely reported that, in regions where invasive species have been introduced and native species have declined, homogenisation of fish populations occurs, resulting in a significant reduction in biodiversity. This loss of diversity disrupts the ecosystem’s stability and resilience, further compounding the negative effects of urbanisation on aquatic environments. However, the impact of urbanisation on fish populations varies depending on the local ecosystem and the degree of urbanisation, necessitating the examination of ecosystem changes induced by urbanisation in each specific region. The Peninsula Malaysia, which is the focus of this study, is a global hotspot for freshwater biodiversity. However, the effects of urbanisation on fish populations in this region have been scarcely studied. The Masai River Basin, which is the subject of this investigation, is located in the Iskandar Development Region, an area undergoing rapid urbanisation. Understanding the consequences of urbanisation on the fish populations and broader ecosystems in this region is critical for providing information for future conservation and management strategies.A fish survey was conducted at 19 sites in the Masai River Basin, which is an urbanised watershed, focusing on river channels that have been straightened or converted into concrete-lined waterways. Additionally, fish surveys were conducted at eight sites in non-urbanised areas for comparison. The survey resulted in the collection of nine orders, 15 families, 28 genera, 32 species and a total of 3,007 individuals. In the urbanised sites, the proportion of native species in the total catch was extremely low, averaging only 10.4% across all sites, with invasive species making up the majority of the individuals captured. This indicates the significant shift in species composition due to urbanisation and the dominance of non-native species in these environments. On the other hand, in the non-urbanised areas, the proportion of native species was high at 88.7%, highlighting the significant impact of urbanisation on the invasion of non-native species. Particularly in the downstream areas of the urbanised watershed, species such as Poecilia sphenops, Mayaheros urophthalmus and Poecilia reticulata were frequently captured. In contrast, at sites in the upstream areas where forested habitats remained intact, native species listed on the IUCN Red List, such as Parambassis siamensis and Clarias batrachus, were captured. The study revealed that urbanisation and development in the targeted watershed are progressing rapidly, underscoring the urgent need for the conservation and restoration of habitats for these native species.